Nurse Caring Experience In Providing Nursing Services Among Covid-19 Patients In The Private Hospital Pekanbaru: A Phenomenological Study - Mersi Ekaputri; Arya Ramadia; Sumandar Sumandar (Science Midwifery, 2021)
The spread of COVID-19 is still continuing very fast. The COVID-19 outbreak is a global problem that has an impact on various life settings and is a challenge for nurses in providing professional nursing care with the risk of contracting and even becoming a victim of COVID-19. The study aims to explore in depth the caring experiences of nurses in providing nursing services to COVID-19 patients in hospital. The research design is used descriptive phenomenology. Participants were 12 nurse, who were selected by purposive sampling technique. The Data be in the form of in-depth interviews and field notes. Furthermore, it is analyzed verbatim and using Colaizzi's approach. The results of the study found six themes, which is nurse anxiety, support system, professional responsibility, workload, refusal of information by patient and patient's family, risk of infection. The themes that emerge from the results of the study can serve as a reference for health workers, especially in the managerial field in taking policies regarding health services, especially nursing services by COVID-19 nurses in order to produce good and safe nursing services for both patients and nurses as nursing service providers.